An improved electrothermal‐coupled model for the temperature estimation of an air‐cooled battery pack. (11th December 2019) - Xie, Yi; Zheng, Jintao; Li, Wei; Lee, Kuining; Zhang, Yangjun; Liu, Jiangyan; Dan, Dan; Wu, Cunxue; Wang, Pingzhong
Summary: This work establishes an improved electrothermal‐coupled model for the estimation of the temperature evolution in an air‐cooled pack with three parallel branches and four serial cells in each branch. This model includes the influences of the cells' state of charge (SOC) and temperature on the ohmic and polarization resistances and polarization capacitance. The current distribution in the pack is considered in the model and applied to predicting the inconsistent effect of cell temperature. Moreover, the pipe network theory is used to model the airflow in the pack and the heat convection between the air and the batteries. An experiment is implemented to verify prediction precision in the electrical and thermal parameters of the pack. The results show that the electrothermal model accurately estimates the electrical and thermal performance of the air‐cooled pack. The relative error of the pack terminal voltage between the prediction and the experiment is 3.22% under the conditions of a discharging rate is 1.5 C (C denotes the ratio of charging/discharging current to battery capacity), environment temperature of 37°C, and air inlet velocity of 6 m/s. Regarding the prediction error in the temperature, the root mean square errors of most batteries are no more than 0.6°C under the conditions of discharge rates of 1 C and 1.5 C and ambient temperatures of 17°C, 27°C, and 37°C.